ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILTAS PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2010-2014 - Kumalasari, Yeyen; Syaichu, Muhamad (Diponegoro Journal of Management, 2016)
This study using Capital Adequacy Ratio (CAR), Liquid Assets to Total Assets (LTA), market share of financing, and Net Interest Margin (NIM) as the independent variable and profitability ratio measured by ROA as the dependent variable. The sample in this study was obtained from a purposive sampling method and obtained five Islamic Banks that qualify as research sample is BCA Syariah, BRI Syariah, Bank Syariah Mandiri, Bank Mega Syariah and Bank Muamalat Indonesia in 2010-2014. This study using secondary data obtained from semi-annual financial statements that can be downloaded from the official website of each bank and the official website of Bank Indoneisa. The analytical method used in this study is Multiple Linear Regression Analysis with a significance level of 5%. The result showed that simultaneously CAR, LTA, market share of financing and NIM has significant effect on ROA of Islamic banks. Partially, variable CAR has negative significant effect, while the LTA, market share of financing and NIM has positive and significant effect on ROA of Islamic banks. Results of regression estimation showed the predictive ability of the model 52.2%, while 47.8% were influenced by other factors outside the model that has not been covered in this research.